Ex Libris Carissimis - Morley, Christopher, 1890-1957 (University of Pennsylvania Press, 2016)
In 1930 A. S. W. Rosenbach founded a Fellowship in Bibliography at the University of Pennsylvania. Christopher Morley was appointed the first fellow under this foundation. The present volume contains the five informal talks Morley delivered, on book collecting and literary anecdotes, at the University in the Autumn of 1931 and also includes a list of the author's eighty-five favorite books.